Influence of Meso and Nanoscale Structure on the Properties of Highly Efficient Small Molecule Solar Cells. Issue 4 (10th December 2015) - Moench, Tobias; Friederich, Pascal; Holzmueller, Felix; Rutkowski, Bogdan; Benduhn, Johannes; Strunk, Timo; Koerner, Christian; Vandewal, Koen; Czyrska‐Filemonowicz, Aleksandra; Wenzel, Wolfgang; Leo, Karl
Abstract : The nanoscale morphology of the bulk heterojunction absorber layer in an organic solar cell (OSC) is of key importance for its efficiency. The morphology of high performance vacuum‐processed, small molecule OSCs based on oligothiophene derivatives (DCV5T‐Me) blended with C60 on various length scales is studied. The analytical electron microscopic techniques such as scanning transmission electron microscopy, energy dispersive X‐ray spectroscopy, highly sensitive external quantum efficiency measurements, and meso and nanoscale simulations are employed. Unique insights into the relation between processing, morphology, and efficiency of the final devices are obtained. It is shown that the connectivity of the oligothiophene‐C60 network is independent of the material domain size. The decisive quantity controlling the internal quantum efficiency is the energetic disorder induced by material mixing, strongly limiting charge and exciton transport in the OSCs. Abstract : The morphology of highly efficient organic solar cells is analyzed with various experimental and theoretical methods. Depositing the absorber layer at selected substrate temperatures (room temperature, 80 °C, and 140 °C) leads to substantial demixing of the absorber layer, increased domain purity, and decreased donor–acceptor interface area.